Development of Fast Alcohol Screening Test Implementation and Electronic Nursing Interventions for Adolescents with Alcohol Abuse: A Literature Review - Triaswati, Rusmai; Hariyati, Rr. Tutik Sri; Daulima, Novy Helena Catharina (STIKep PPNI Jawa Barat, 2024)
Aims: This literature review aims to theoretically analyze the rationale for developing this electronic application to cover all aspects of adolescent mental health life and as a promotive and preventive tool for adolescents with alcohol abusers. Methods: The literature review method was carried out on ten articles which were obtained from five databases namely PUBMED, Google Scholar, ClinicalKey Nursing, ProQuest, Science Direct. The keywords for article search were